Optimal scheduling of combined heat and power plants using mixed-integer nonlinear programming - Kim, Jong Suk; Edgar, Thomas F. (Energy (Oxford), 2014)
This paper presents the application of MINLP (mixed-integer nonlinear programming) approach for scheduling of a CHP (combined heat and power) plant in the day-ahead wholesale energy markets. This work employs first principles models to describe the nonlinear dynamics of a CHP plant and its individual components. The MINLP framework includes practical constraints such as minimum/maximum power output and steam flow restrictions, minimum up/down times, start-up and shut-down procedures, and fuel limits. Special care is given to the explicit modeling of the unit start-up types (hot, warm, and cold), which depend on the component's prior reservation time, resulting in the differences in the time-dependent start-up costs of generating units. The model also accounts for the different operating modes (synchronization, soak, dispatch, and desynchronization) during start-up and shut-down of each unit. We provide case studies involving the Hal C. Weaver power plant complex at the University of Texas at Austin to demonstrate the effectiveness of the proposed methodology. The results show that the optimized operating strategies can yield substantial net incomes from electricity sales. •Optimal scheduling of a CHP (combined heat and power) plant in the wholesale energy markets is proposed.•A mixed-integer nonlinear programming model is built to optimize power production.•Power production is maximized during on-peak hours due to high electricity prices.•The maximum profit is realized by committing more efficient generating units.•Less efficient generating units can be brought on-line due to operating constraints.